Characterizing the role of Pdgfra in calvarial development. Issue 5 (19th January 2023) - Umar, Meenakshi; Bartoletti, Garrett; Dong, Chunmin; Gahankari, Apurva; Browne, Danielle; Deng, Alastair; Jaramillo, Josue; Sammarco, Mimi; Simkin, Jennifer; He, Fenglei
Abstract: Background: Mammalian calvarium is composed of flat bones developed from two origins, neural crest, and mesoderm. Cells from both origins exhibit similar behavior but express distinct transcriptomes. It is intriguing to ask whether genes shared by both origins play similar or distinct roles in development. In the present study, we have examined the role of Pdgfra, which is expressed in both neural crest and mesoderm, in specific lineages during calvarial development. Results: We found that in calvarial progenitor cells, Pdgfra is needed to maintain normal proliferation and migration of neural crest cells but only proliferation of mesoderm cells. Later in calvarial osteoblasts, we found that Pdgfra is necessary for both proliferation and differentiation of neural crest‐derived cells, but not for differentiation of mesoderm‐derived cells. We also examined the potential interaction between Pdgfra and other signaling pathway involved in calvarial osteoblasts but did not identify significant alteration of Wnt or Hh signaling activity in Pdgfra genetic models. Conclusions: Pdgfra is required for normal calvarial development in both neural crest cells and mesoderm cells, but these lineages exhibit distinct responses to alteration of Pdgfra activity. Key Findings: Our study showed that Pdgfra plays essential and distinct roles in progenitors and osteoblasts from different origin during calvarial development. We found Pdgfra is required to maintain cell proliferation of both neural crest and mesoderm cells, but only needed for neural crest cell migration.